Optimization of Commercial Feed with Moringa Leaf Powder (Moringa oleifera) for the Growth of Nilem Fish Fingerlings (Osteochilus hasselti) - Perdana, Adli Waliul; Syafitria, Afriani; Akbar, Said Ali (JURNAL AKUAKULTURA, 2024)
This study aims to test the impact of these additions on the growth of nilem fish Fingerlings. The research design was a completely randomized design (CRD) with six treatments and three replicates by adding moringa leaf meal (0%, 2%, 4%, 6%, 8%, and 10%) to commercial feed. The characteristics observed in this study included feed conversion ratio (FCR), specific growth rate, survival rate (SR), absolute length and weight growth, and water quality. Analysis of variance (ANOVA) was used to evaluate the data, and Duncan's test was performed subsequently. The results showed that although there was no significant effect (P>0.05) on tilapia fry or survival rate (SR), the addition of moringa leaf meal to commercial feed had a significant effect (P<0.05) on tilapia larval growth in terms of absolute length and weight growth, specific growth rate, and Feed Conversion Ratio (FCR). The ideal composition for nilem Fingerlings development was 6%; the absolute values for length and weight growth were 1.13 cm and 0.33 g, the specific growth rate was 1.27%/day, the FCR was 1.41, and the survival rate of nilem fry was 93.33%.